Liquid inoculant containing of Azospirillum brasilense strain, via seeds in the corn crops, associated with nitrogen fertilization promoting productivity gains (Research, Society and Development, 2021)
The objective was to evaluate the efficiency in the field of the liquid inoculant with the strains Ab-V5 and Ab-V6 of Azospirillum brasilense, for corn, through seed treatment, associated with nitrogen fertilization. They were conducted in a randomized block design with seven treatments and four replications. T1 - 0 kg ha-1 of nitrogen, without inoculation (control); T2 - 80 kg ha-1 of N, without inoculation; T3 - 160 kg ha-1 of N; T4 - 80 kg ha-1 of N + Inoculation registered standard liquid, containing A. brasilense (Ab-V5 and Ab-V6), 100 mL 25 kg-1 of seeds; T5 - 80 kg ha-1 of N + FERTIBIO Azospirillum 'Liquid' in 100 mL 25 kg-1 of seeds; T6 - 80 kg ha-1 of N + FERTIBIO Azospirillum 'Liquid' 150 mL 25 kg-1 of seeds; and T7 - ​​80 kg ha-1 of N + FERTIBIO Azospirillum 'Liquid' 200 mL 25 kg-1 of seeds. The liquid inoculant  showed efficiency similar to the registered standard inoculant, when it was used, via seed inoculation with supplementation of 80 kg ha-1 of nitrogen. This one stood out, being statistically superior to the control and to the treatment where half the dose of nitrogen recommended was provided, without inoculation. According to the results, the efficiency of the liquid inoculant (strains Ab-V5 and Ab-V6) of A. brasilense, being recommended the dose of 100 mL 25 kg-1 of inoculant seeds, via seed treatment, for the corn crop, using half the dose of nitrogen fertilizer for the crop.